The Castaway Syndrome. Robinson Crusoe and Julian Ursyn Niemcewicz - Dąbrowicz, Elżbieta (Porównania, 2019)
The success of Daniel Defoe’s novel meant that its protagonist began to live as an emblematic figure for Western culture (especially English culture) expanding beyond the borders of Europe. Robinson epitomised a set of features guaranteeing success in the conquest of the world, a combination of individualism, entrepreneurship and Protestant religiosity. Despite the fact that the Polish mentality of noble origin had an anti-bourgeois bias, Defoe’s novel gained popularity also among Polish readers. Robinson Crusoe was an ally of those Polish writers who first worked to save the state at the end of the 18th century, and when they failed, at least tried to modernize the Polish mentality. One of them, Julian Ursyn Niemcewicz, treated Robinson Crusoe as a borderline character between fiction and extra-literary truth. He, like Robinson, travelled to the New World and tried to survive there. In his diary and epistolary notes there are many motifs that are considered in connection with Defoe’s novel: migrations, ethnic conditions of colonisation, the attitude of newcomers to the indigenous inhabitants. It is also worth looking at the novel Jan z Tęczyna by Niemcewicz through the lens of Robinson Crusoe. The protagonist, like Robinson, is shipwrecked on an island. However, he does not manage to settle on the island because of internal obstacles: idealistic ideas about loving a woman and his own status as a Pole of an excellent family.